Preparation method of liquid metal / ionic liquid composite lubricating function additive with three-layer core-shell structure
By combining three metal alloys, gallium, indium and tin, with 1-hexyl-3-methylimidazole hexafluorophosphate ([HMIM]PF6) ionic liquid components, a three-layer core-shell structure liquid metal/ionic liquid was prepared. The composite lubrication functional additive solves the problem of poor lubricity of liquid metal lubricants under low load conditions, and achieves excellent lubricating performance and low-cost production under extreme operating conditions.
Patent Information
- Application Number
- CN202411553673.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-03
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-03
AI Technical Summary
Existing liquid metal lubricants have poor lubricity under low load conditions and are costly, making it difficult to meet the lubrication needs under extreme operating conditions.
Liquid metal/ionic liquid composite lubrication functional additive using a three-layer core-shell structure, by combining three metal alloys of gallium, indium and tin with 1-hexyl-3-methylimidazole hexafluorophosphate ([HMIM]PF6) ionic liquid Combining components, the composite lubricating additives are prepared by ultrasonic dispersion.
It achieves excellent lubricating performance under extreme operating conditions, including improving anti-wear and friction reduction performance and load bearing capacity, and is simple in preparation and low in cost, suitable for industrial-scale production.
Smart Images

Figure CN119432469A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of high-performance lubricating materials under extreme working conditions, and specifically relates to a method for preparing a liquid metal / ionic liquid composite lubricating functional additive with a three-layer core-shell structure. Background Art
[0002] Liquid metal (LM) refers to an alloy material mainly composed of gallium and other metal elements. LM also has the characteristics of low melting point, high temperature resistance, high electrical conductivity, high thermal conductivity, biocompatibility, low volatility and fluidity. LM has been widely studied in the field of tribology and can be added to grease, polyalphaolefin (PAO), water and polyimide (PI) to improve the lubrication properties of composites [Yin, F., Zhao, Y., Li, Z., & Li, T. (2022). Study on external influencing factors of gallium based liquid metal as lubricant. Journal of Functional Materials, 53(2), 2043-2049. https: / / doi.org / 10.3969 / j.issn.1001-9731.2022.02.007][Xiao, R., Yao, M., Cheng, J., et al. (2024). Lubrication properties of gallium-based liquid metals by doping bismuth. Tribology International, 195, 109653]
[0003] Tian et al. added gallium-based liquid metal to grease in different proportions and investigated the tribological properties of the composite on a four-ball friction tester. When liquid metal was added, the extreme pressure lubrication ability of the grease was effectively improved, but the anti-wear performance under low load was not significantly improved [Bai, PP, Li, SW, Jia, WP, et al. (2018). Tribological properties of liquid-metal galinstan as novel additive in lithium grease. Tribology International, 128, 181-189]. The research group of Academician Liu Weimin studied the influence of aluminum doping in liquid metal on its tribological behavior. At the same time, the changes in the lubrication performance of liquid metal under high load conditions were also explored [Cheng, J., Yu, Y., Guo, J., Wang, S., Zhu, S., Ye, Q., Yang, J., & Liu, W. (2019). Ga-based liquid metal with good self-lubricity and high load-carrying capacity. Tribology International, 129, 1-4.]. In summary, liquid metal has good anti-wear properties. However, liquid metal alloys are expensive and have poor lubricity under low loads.
[0004] Ionic liquids (ILs) have similar physical and chemical properties to liquid metals, such as low volatility and good lubrication properties [Xiao, H., Guo, D., Liu, S., Pan, G., & Lu, X. (2011). Film thickness of ionic liquids under high contact pressures as a function of alkyl chain length. Tribology Letters, 41 (2), 471–477.]. Ionic liquids are usually organic salts composed of several anions and organic cations. They have a melting point generally below 100 °C, are semi-fluid, non-toxic, and non-volatile. They can be used as lubricating functional additives, especially lubricating additives under extreme working conditions [Guo, H., & Iglesias, P. (2021). Ionic liquids as high-performance lubricants and lubricant additives. In Intech Open. https: / / doi.org / 10.5772 / intechopen.96428].
[0005] Musavi et al. tried to use ionic liquid as a green, cutting fluid-compatible additive for grinding. Compared with mineral-based additives, ionic liquid additives can reduce grinding forces and improve workpiece surface integrity. The reason can be attributed to the fact that compared with mineral-based fluids, liquid molecules tend to adhere to the surface of high-temperature alloys, forming a strong lubricating layer with a lower static contact angle, thereby creating stable lubrication conditions in the high-stress grinding affected area [Musavi, SH, Razfar, M., & Domiri Ganji, D. (2024). New application of ionic liquid as a green-efficient lubricant. Results in Engineering, 21, 101773]. It can be found from the literature that phosphates can be adsorbed on the surface of metal oxide layers to modify the surface of particles [Li, MX, Liu, JY, Xu, YF, et al. (2016). Phosphate adsorption on metal oxides and metal hydroxides: A comparative review. 24 (3), 319-332].
[0006] In view of this property, it is envisioned that the core-shell structured particles prepared by adsorbing the ionic liquid component on the liquid metal interface can be used as lubricating functional additives, and there are few related research reports. Therefore, the successful preparation of this composite additive can develop a good lubricating additive under extreme working conditions, providing a basic guarantee for the good operation of high-end equipment. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a functional additive with good lubrication effect and capable of satisfying lubrication under extreme working conditions. Therefore, the present invention proposes a preparation method of a liquid metal / ionic liquid composite lubrication functional additive with a three-layer core-shell structure.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] A method for preparing a liquid metal / ionic liquid composite lubricating functional additive with a three-layer core-shell structure, comprising the following steps:
[0010] 1) Weigh gallium, indium and tin respectively and place them in a container, heat them up and stir them at the same time, and stop heating after all the metals are fully mixed; cool them to room temperature to obtain a Ga-In-Sn ternary alloy, which is liquid metal (LM);
[0011] 2) Take a certain mass of liquid metal (LM), place it in 1-hexyl-3-methylimidazolium hexafluorophosphate ([HMIM]PF6), stir it for a period of time, and then place it in a CNC ultrasonic cleaning machine for water bath ultrasonication to obtain a liquid metal / ionic liquid composite lubricating functional additive with a three-layer core-shell structure.
[0012] As a preferred technical solution of the present invention, in the preparation method:
[0013] The mass ratio of gallium, indium and tin in step 1) is 68.5-80:21.5-30:10-20. The heating temperature during stirring is 80-160° C. The Ga-In-Sn ternary alloy obtained after cooling to room temperature is directly used for continuous preparation in step 2). If continuous preparation is not possible, it needs to be stored in alkaline solution.
[0014] In step 2), the amount of liquid metal (LM) added is 0.1% to 1% of the mass of 1-hexyl-3-methylimidazolium hexafluorophosphate ([HMIM]PF6). After the liquid metal (LM) and 1-hexyl-3-methylimidazolium hexafluorophosphate ([HMIM]PF6) are mixed, they are first mechanically stirred for 3-6 hours, and then placed in a CNC ultrasonic cleaning machine for water bath ultrasonication for 3-6 hours.
[0015] The present invention utilizes the advantages of liquid metal such as low melting point, high temperature resistance, and easy flow, and adopts a simple ultrasonic dispersion method to prepare a liquid metal / ionic liquid composite lubricating functional additive. At the same time, a scanning electron microscope and an accompanying energy spectrum are used to characterize the surface condition of the ionic liquid modified liquid metal; on a four-ball friction tester, the extreme pressure performance and anti-wear and friction reduction characteristics of the ionic liquid with different addition amounts of liquid metal are explored. Compared with the prior art, the excellent effects of the present invention are mainly manifested in:
[0016] 1) The liquid metal / ionic liquid composite lubricating functional additive prepared by the present invention has a diameter of about 500nm, and a layer of ionic liquid film adheres to the surface of the liquid metal. Analysis of the worn surface of the steel ball shows that the organic groups attached to the surface of the friction pair after adding LM can effectively protect the interface of the friction pair, and the boundary lubrication film generated by the friction-induced chemical reaction can effectively improve the load-bearing capacity and anti-wear and friction-reducing performance of the lubricant. Its excellent lubrication performance makes it more widely used in existing fields or unknown fields.
[0017] 2) The present invention adopts ultrasonic preparation, which is simple and easy, low in cost, and can also make LM particles evenly distributed in [HMIM]PF6, so as to further improve the lubrication performance of the composite lubricating additive. The preparation method proposed by the present invention is pollution-free, and the prepared product is an environmentally friendly green composite lubricating additive. LM has superior dispersibility in [HMIM]PF6 and can be stored for a long time at room temperature. At the same time, the preparation process uses cheap and easy-to-obtain instruments, has low production costs, and is suitable for industrial-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a transmission picture of the liquid metal / ionic liquid composite lubricating functional additive prepared by the present invention dispersed in dichloromethane. As shown in the figure, the LM particles have a clear core-shell structure, and a transparent coating layer of about 20 nm is clearly visible on the surface. The element distribution diagram shows that the surface elements are mainly composed of C, O, F, and P, which indicates that a layer of [HMIM]PF6 is self-assembled on the surface of the LM particles.
[0019] Figure 2 This is a transmission image of the liquid metal / ionic liquid composite lubricating functional additive prepared by the present invention dispersed in anhydrous ethanol. It can be clearly seen that most of the surface-coated [HMIM]PF6 has been detached and agglomerated together. Figure 2 In (b), there is still an oxide layer of about 5 nm where the [HMIM]PF6 coating is lost. Figure 1 Because of the [HMIM]PF6 coating, it cannot be clearly observed. Figure 1 and Figure 2It can be seen that the liquid metal / ionic liquid composite lubricating functional additive prepared by the present invention has a three-layer core-shell structure as a whole, wherein the core is a liquid alloy composed of three metal elements: gallium, indium and tin, the middle layer is an oxide layer formed by natural oxidation of the liquid alloy, and the outermost layer is 1-hexyl-3-methylimidazole hexafluorophosphate ([HMIM]PF6) adsorbed on the oxide layer.
[0020] Figures 3 to 6 Anti-wear and friction reduction tests were conducted on several composite lubricating additives of different concentrations prepared in the embodiments of the present invention at loads of 392N, 784N, 1568N, and 1960N in comparison with the commercial additive ZDDP.
[0021] Depend on Figure 3 (a) It can be seen that the friction coefficient curve of [HMIM]PF6 with 0.2wt% LM and 0.3wt% LM added under a load of 392N is at the lowest position among several samples, and remains stable at around 0.06; the friction coefficient curve of [HMIM]PF6 with 1wt% commercial additive ZDDP added is higher, about 0.07; Figure 3 (b) shows the average friction coefficient (ACOF) and average wear spot diameter (AWSD) of [HMIM]PF6 at different LM addition amounts. It can be seen that under a load of 392N, as the amount of LM addition increases, the ACOF and AWSD of [HMIM]PF6 also increase. Adding 0.2wt% and 0.3wt% LM can effectively improve the anti-wear and friction reduction properties of [HMIM]PF6, among which the addition amount of 0.2wt% has the best effect. After adding 0.2wt% LM, ACOF decreased by 16.9% from 0.071 to 0.059, and the wear spot diameter decreased by 31.3% from 454.274μm to 311.97μm. Figure 4 It can be seen that under a load of 784N, adding 0.3wt% LM achieves the minimum ACOF, which decreases from 0.057 to 0.054, a decrease of 5.3%; adding 0.2wt% LM achieves the minimum AWSD, which decreases from 529.789μm to 479.438μm, a decrease of 9.5%. Figure 5 It shows that adding different contents of LM has little effect on the anti-wear properties of [HMIM]PF6, and the AWSD of the steel ball has almost no change at several different addition amounts. However, adding 0.3wt% LM under this load can effectively reduce the ACOF of [HMIM]PF6, and its value drops from 0.055 to 0.046, a decrease of 16.4%. Figure 6 It shows that the AWSD of ACOF and steel ball reached the lowest value when LM was added in an amount of 0.3wt%, decreasing by 10.6% (from 0.066 to 0.059) and 11.9% (from 885.401μm to 779.763μm), respectively. DETAILED DESCRIPTION
[0022] Example 1
[0023] This example provides a liquid metal / ionic liquid composite lubricating functional additive, and the specific steps are as follows:
[0024] 1) Weigh gallium, indium and tin in a mass ratio of 68.5:21.5:10 respectively and place them in a beaker. Then place the beaker on an electric heating plate and heat it at 80°C. Stir with a glass rod. After all the metals are fully mixed, stop heating. After cooling, add sodium hydroxide solution to remove the oxides produced during the heating process to obtain a Ga-In-Sn ternary alloy (LM).
[0025] 2) Add 0.03 g of LM to 30 g of 1-hexyl-3-methylimidazolium hexafluorophosphate [HMIM] PF6, and stir the mixture mechanically for 3 h using an electric stirrer.
[0026] 3) The stirred solution was placed in a CNC ultrasonic cleaning machine for 3 hours in a water bath to obtain the prepared three-layer core-shell structure LM / [HMIM]PF6 composite lubricating additive. (The appearance, morphology, structure, lubrication performance and other tests are similar to Figure 1-6 shown).
[0027] Example 2
[0028] This example provides a liquid metal / ionic liquid composite lubricating functional additive, and the specific steps are as follows:
[0029] 1) Weigh gallium, indium and tin in a mass ratio of 68.5:21.5:10 respectively and place them in a beaker. Then place the beaker on an electric heating plate and heat it at 105°C. Stir with a glass rod and stop heating after all the metals are fully mixed. After cooling, add sodium hydroxide solution to remove the oxides produced during the heating process to obtain a Ga-In-Sn ternary alloy (LM).
[0030] 2) Add 0.06 g of LM to 30 g of 1-hexyl-3-methylimidazolium hexafluorophosphate [HMIM] PF6, and stir the mixture mechanically for 3.5 h using an electric stirrer.
[0031] 3) The stirred solution was placed in a CNC ultrasonic cleaning machine for 3.5 hours in a water bath to obtain the prepared three-layer core-shell structure LM / [HMIM]PF6 composite lubricating additive. (The appearance, morphology, structure, lubrication performance and other tests are similar to Figure 1-6 shown).
[0032] Example 3
[0033] This example provides a liquid metal / ionic liquid composite lubricating functional additive, and the specific steps are as follows:
[0034] 1) Weigh gallium, indium and tin in a mass ratio of 68.5:21.5:10 respectively and place them in a beaker. Then place the beaker on an electric heating plate and heat it at 120°C. Stir with a glass rod and stop heating after all the metals are fully mixed. After cooling, add sodium hydroxide solution to remove the oxides produced during the heating process to obtain a Ga-In-Sn ternary alloy (LM).
[0035] 2) Add 0.09 g of LM to 30 g of 1-hexyl-3-methylimidazolium hexafluorophosphate [HMIM] PF6, and stir the mixture mechanically for 5 h using an electric stirrer.
[0036] 3) The stirred solution was placed in a CNC ultrasonic cleaning machine for 4 hours in a water bath to obtain the prepared three-layer core-shell structure LM / [HMIM]PF6 composite lubricating additive. (The appearance, morphology, structure, lubrication performance and other tests are similar to Figure 1-6 shown).
[0037] Example 4
[0038] This example provides a liquid metal / ionic liquid composite lubricating functional additive, and the specific steps are as follows:
[0039] 1) Weigh gallium, indium and tin in a mass ratio of 68.5:21.5:10 respectively and place them in a beaker. Then place the beaker on an electric heating plate and heat it at 130°C. Stir with a glass rod and stop heating after all the metals are fully mixed. After cooling, add sodium hydroxide solution to remove the oxides produced during the heating process to obtain a Ga-In-Sn ternary alloy (LM).
[0040] 2) Add 0.12 g of LM to 30 g of 1-hexyl-3-methylimidazolium hexafluorophosphate [HMIM] PF6, and stir mechanically for 4 h using an electric stirrer.
[0041] 3) Place the stirred solution in a CNC ultrasonic cleaning machine and perform water bath ultrasonic treatment for 5 hours to obtain the prepared three-layer core-shell structure LM / [HMIM]PF6 composite lubricating additive. (The appearance, morphology, structure, lubrication performance and other tests are similar to Figure 1-6 shown).
[0042] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a three-layer core-shell structured liquid metal / ionic liquid composite lubricating functional additive, characterized in that: Here are the steps: 1) Weigh gallium, indium and tin respectively and place them in a container, heat them up and stir them at the same time, and stop heating after all the metals are fully mixed; cool them to room temperature to obtain a Ga-In-Sn ternary alloy, which is liquid metal (LM); 2) Take a certain mass of liquid metal (LM), place it in 1-hexyl-3-methylimidazolium hexafluorophosphate ([HMIM]PF6), stir it for a period of time, and then place it in a CNC ultrasonic cleaning machine for water bath ultrasonication to obtain a liquid metal / ionic liquid composite lubricating functional additive with a three-layer core-shell structure.
2. The preparation method according to claim 1, characterized in that In step 1), the mass ratio of gallium, indium and tin is 68.5-80:21.5-30:10-20.
3. The preparation method according to claim 1, characterized in that: The heating temperature during stirring in step 1) is 80-160°C.
4. The preparation method according to claim 1, characterized in that: The Ga-In-Sn ternary alloy obtained in step 1) after cooling to room temperature is directly used for continuous preparation in step 2). If continuous preparation is not possible, it needs to be stored in alkaline solution.
5. The preparation method according to claim 1, characterized in that: In step 2), the amount of liquid metal (LM) added is 0.1% to 1% of the mass of 1-hexyl-3-methylimidazolium hexafluorophosphate ([HMIM]PF6).
6. The preparation method according to claim 1, characterized in that: In step 2), the liquid metal (LM) and 1-hexyl-3-methylimidazolium hexafluorophosphate ([HMIM]PF6) are mixed and first mechanically stirred for 3-6 hours, and then placed in a CNC ultrasonic cleaning machine for water bath ultrasonication for 3-6 hours.
7. The liquid metal / ionic liquid composite lubricating functional additive prepared by the method according to any one of claims 1 to 6, characterized in that: The overall structure is a three-layer core-shell structure. The core is a liquid alloy composed of three metal elements: gallium, indium and tin. The middle layer is an oxide layer formed by natural oxidation of the liquid alloy, and the outermost layer is 1-hexyl-3-methylimidazolium hexafluorophosphate ([HMIM]PF6) adsorbed on the oxide layer.
Citation Information
Patent Citations
Halogen free ionic liquids as lubricant or lubricant additives and a process for the preparation thereof
US20170096614A1
Conductive ink, and preparation method therefor and use thereof
WO2024152687A1
Ternary bi-in-sn nanoalloy material and liquid-phase ultrasonic preparation method therefor
WO2024174287A1